Ways to Increase Railway Competitiveness - Nesterenko, Halyna I.; Muzykin, Mykhailo I.; Strelko, Oleh; Shcherbyna, Rozalia; Pavlenko, Olena (Державний університет інфраструктури та технологій, Київ, 2022)
ENG: Nowadays, railway transport is the most developed in Ukraine. It is the heart of transport services for individuals and legal entities, without it is difficult to imagine the normal functioning of production facilities and logistics firms. Rail transport also occupies the main place among domestic traffic. Passenger transportation occupies a significant place in the work of transport, so suburban transportation occupies the second place in terms of mass transportation after intercity transportation by automobile transport . The demand for this type of transportation can be called elastic, since there is an impact of seasonality on transportation, for example, the beginning and ending of academic semesters, vacation time. Therefore, it is advisable to consider tourist trains that could run on sections of the Dnіpro-Pіvdennij station – Apostolovo station, Dnіpro-Pіvdennij station – Surskoye station, Dnіpro-Pіvdennij station – Zhovtokamenka station, Dnіpro-Pіvdennij station – Elizarovo station. The article provides graphs of the movement of these trains, allowing passengers to visit attractions along the entire route. Consequently, tourist routes can improve the development of tourism throughout Ukraine, and not popular destinations. This may result in increased demand for tourist trains, increased monetization of passenger transportation, thereby improving passenger comfort.

UKR: На сьогодні залізничний транспорт є найрозвинутішим в Україні. Він є серцем транспортних послуг для фізичних та юридичних осіб, без нього важко уявити нормальне функціонування виробництв та логістичних фірм. Залізничний транспорт також займає головне місце серед перевезень внутрішніх сполучень. Пасажирські перевезення займають вагоме місце в роботі транспорту, тож приміські перевезення займають друге місце за масовістю після внутрішньоміських перевезень автотранспортом. Попит на такий вид перевезень можна назвати еластичним, оскільки є вплив сезонності на перевезення, наприклад початок і закінчення навчальних семестрів, канікулярний час та час відпусток. Тож доцільно розглянути туристичні поїзди, що мали б змогу курсувати на ділянках ст. Дніпро-Південний – ст. Апостолово, ст. Дніпро-Південний – ст. Сурське, ст. Дніпро-Південний – ст. Жовтокам`янка, ст. Дніпро-Південний – ст. Елизарово. В статті наведені графіки руху даних поїздів, що дозволяють пасажирам відвідати пам'ятки на всьому шляху прямування. Отже, туристичні маршрути можуть покращити розвиток туризму по всій Україні, а не тільки на популярних напрямках. Результатом чого можуть стати збільшений попит на туристичні поїзди, збільшена монетизація пасажирських перевезень, за рахунок чого можливість покращення комфорту пасажирів.
Шляхи підвищення конкурентоздатності залізниці
H. Nesterenko: ORCID 0000-0003-1629-0201; M. Muzykin: ORCID 0000-0003-2938-7061; О. Strelko: ORCID 0000-0003-3173-3373; R. Shcherbyna: ORCID 0000-0003-4505-921X; О. Pavlenko: ORCID 0000-0002-6509-9406
Keywords: railway transport; passenger transportation; tourist trains; tourist routes; залізничний транспорт; пасажирські перевезення; туристичні поїзди; туристичні маршрути; КТСЛ; TECHNOLOGY